Grain boundary relaxation and reconstruction: effect on local magnetic moment - Vitkovská, E.; Ballo, P. (Condensed Matter Physics, 2016)
We present a detailed numerical study on structure and local magnetic properties of 〈100〉 symmetric tilt grain boundaries in bcc-iron. Particular attention is paid to connection between type of grain boundary relaxation and local magnetic properties. Results from first principles calculation showed that grain boundary reconstruction leads to non-uniform distribution of local magnetic moments in grain boundary plane. This is in contrast with the result obtained in grain boundary plane, where simple relaxation is observed. Well optimized atomic configurations in the vicinity of the interface were achieved by simulated annealing optimization technique improved by combination with genetic algorithm.